Cms1 coordinates stepwise local 90S pre-ribosome assembly with timely snR83 release - Lau, Benjamin; Beine-Golovchuk, Olga; Kornprobst, Markus; Cheng, Jingdong; Kressler, Dieter; Jády, Beáta; Kiss, Tamás; Beckmann, Roland; Hurt, Ed (Cell reports, 2022)
Ribosome synthesis begins in the nucleolus with 90S pre-ribosome construction, but little is known about how the many different snoRNAs that modify the pre-rRNA are timely guided to their target sites. Here, we report a role for Cms1 in such a process. Initially, we discovered CMS1 as a null suppressor of a nop14 mutant impaired in Rrp12-Enp1 factor recruitment to the 90S. Further investigations detected Cms1 at the 18S rRNA 3′ major domain of an early 90S that carried H/ACA snR83, which is known to guide pseudouridylation at two target sites within the same subdomain. Cms1 co-precipitates with many 90S factors, but Rrp12-Enp1 encircling the 3′ major domain in the mature 90S is decreased. We suggest that Cms1 associates with the 3′ major domain during early 90S biogenesis to restrict premature Rrp12-Enp1 binding but allows snR83 to timely perform its modification role before the next 90S assembly steps coupled with Cms1 release take place.
Gesehen am 23.01.2023